2019
DOI: 10.1590/1678-992x-2017-0322
|View full text |Cite
|
Sign up to set email alerts
|

Carbon indices to assess quality of management systems in a Subtropical Acrisol

Abstract: Management systems to improve soil quality are essential for agricultural and environmental sustainability. We assessed the quality of soil management systems applied to a subtropical Acrisol in terms of the carbon management index (CMI), the stratification ratio for total organic carbon (SR-TOC) and light fraction of organic matter (SR-LF). In addition, we examined their relationship to chemical, physical and biological soil quality indicators, as well as to maize yield. The study was conducted on a long-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…These results are in line with the findings of Zanatta et al (2019) who indicated that N fertilization was able to contribute about 8-33% improvement in soil quality better than no fertilizer under similar soil condition in Brazil. Furthermore, these results also corroborate with the findings of Adjei-Nsiah et al (2007) who identified N and K as playing major roles in sustaining crops yield under cassava-maize rotation in Ghana.…”
Section: Regression Analysis Among the Soil Nutrients With CMIsupporting
confidence: 92%
“…These results are in line with the findings of Zanatta et al (2019) who indicated that N fertilization was able to contribute about 8-33% improvement in soil quality better than no fertilizer under similar soil condition in Brazil. Furthermore, these results also corroborate with the findings of Adjei-Nsiah et al (2007) who identified N and K as playing major roles in sustaining crops yield under cassava-maize rotation in Ghana.…”
Section: Regression Analysis Among the Soil Nutrients With CMIsupporting
confidence: 92%
“…Higher CMI values mean higher soil quality, whereas lower values indicate lower soil quality (ASSMANN et al, 2014). CMI also indicates increased lability of organic matter, as it is highly correlated with the C-MOP stock (SILVA et al, 2016) and positively correlated with several chemical, physical and biological attributes of the soil (ZANATTA et al, 2019). In this study, all treatments with the use of turkey litter indicated improvement in soil organic matter quality, especially at the highest dose evaluated (69.24 Mg ha -1 ) and in all layers evaluated, reaching increments of 156% compared to the control treatment, in the 0.1-0.2 m layer.…”
Section: Resultsmentioning
confidence: 99%
“…For this, other attributes have been used, such as the C and N stocks in particulate organic matter (POC and N-POM) and the C management index (CMI) (ASSMANN et al, 2014;SOUZA et al, 2016). CMI is considered a sensitive attribute because it is correlated with other physical, chemical and biological indicators of soil quality (ZANATTA et al, 2019).…”
Section: Introductionmentioning
confidence: 99%